2000
DOI: 10.1136/bmj.321.7259.505
|View full text |Cite
|
Sign up to set email alerts
|

Reducing error, improving safety

Abstract: Defensive culture of British medicine needs to change Editor-It was brave to devote a whole issue to medical error 1-how to recognise, how to investigate, how to analyse, and how to change systems to improve patient safety. 1 However, we regret that the edition was dominated by American studies, ignoring the British contribution of confidential inquiries and analyses of closed claims, which have significantly improved safety in some well defined areas of medical practice. In the United States the insurance ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Various studies, however, showed that as an institution improves in the care it delivers and its safety culture more problems may be reported since open reporting is a tenet of safe practice [40]. Increased incident reporting rates may not be indicative of an unsafe organization, but may reflect a shift in organizational culture [41]. In this context it is important to note that the total number of reported incidents more than doubled while the contribution of technical factors to incident causation remained constant.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies, however, showed that as an institution improves in the care it delivers and its safety culture more problems may be reported since open reporting is a tenet of safe practice [40]. Increased incident reporting rates may not be indicative of an unsafe organization, but may reflect a shift in organizational culture [41]. In this context it is important to note that the total number of reported incidents more than doubled while the contribution of technical factors to incident causation remained constant.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increasing HCOs' performances obviously also requires dealing with the reduction of medical errors. The British Medical Journal very recently devoted a whole issue to this fundamental challenge: how to recognize, investigate, analyze, and change systems to improve patient safety [28]. The error problem can be viewed in two ways: the human approach and the system approach [29].…”
Section: Performance Assessmentmentioning
confidence: 99%
“…Health caremustbedelivered by systems thatare carefullyand consciously designed to be certifiablys afe [ 8,9], effective, efficient, andequitable [2]. Such systemsmust be designedt os erve the needso fp atients [10],and thismeans: to ensure thatpatients aref ullyi nformed,r etainc ontrol andp articipate in caredeliverywheneverpossible, andthattheyreceive carethatisrespectful of their valuesa nd preferences [2].…”
Section: Introductionmentioning
confidence: 99%